Asuhan Keperawatan Pada Ny. I dengan Gangguan Sistem Reproduksi Post Operasi Histrektomi Hari Ke-1 Indikasi Mioma Uteri di Ruang Sofa RS.PKU Muhammadiyah Surakarta - Agustina, Ika Putri; , Dian Hudiyawati, S.Kep., Ns., M.Kep (2013)
Background : Myoma uterine is a benign tumor that grows in the womb. The cause of the relationship of reproductive hormones (estrogen) and often occurs in women of reproductive age over the age of 35 years. Myoma uteri danger is if not addressed promptly can lead to iron deficiency anemia due to abnormal bleeding of the uterus and during the reproductive age can cause infertility. Aim of Research : To study about nursig care on client with mioma uteri post operation histrektomi day-1 including assessment, intervention, implementation, and evaluation. Result : After the nursing care during 3x24 jam showed decreased patient pain scale from scale 7 to scale 3, the patient can perform the movement and activities of daily rising and there is no infection in patients. Conclusion : histrektomi surgery is one treatment of myoma uterine, coorporation between the health care team, patient and families are very necessary for the success of nursing care to patient. Deep breathing relaxation techniques can reduce the pain felt by the patient, physical mobilization exercises to train the patient to improve the movement, keep the environment clean to pervent the risk of infection. Problems are found three clients can be resolved.